Urban Waterfronts: Contemporary Streams of Planning Conflicts. (November 2019) - Avni, Nufar; Teschner, Na'ama
Since the 1970s, urban waterfronts have undergone profound functional transformations. While in many ways they have been proven successful in reviving prime urban areas, waterfront redevelopments have also been contested. This article reviews several aspects of the planning conflicts that have been pertinent to the redevelopment of waterfronts internationally: (1) land ownership, (2) heritage and culture, (3) social and environmental justice, and (4) environment and resilience. Based on a comprehensive review of state-of-the-art literature, we suggest that the growing concerns over social justice and environmental resilience during the course of waterfront redevelopments will continue to challenge cities in the future.